Effect of Double Bond Equivalent of Biodiesels on their Heating Value and Cetane Number - Gopinath, A.; Sairam, K.; Velraj, R. (Asian Journal of Chemistry, 2013)
The mono-alkyl esters of vegetable oils defined as biodiesels are accepted as alternative energy sources for petro-diesel and growing in a stable manner across the globe. The properties of biodiesel depend mainly upon structure of its components and composition. In the present study, the effect of double bond equivalent of biodiesels on their heating value and cetane number was investigated. Double bond equivalents are essentially identical to the iodine value, the major difference being that the molecular weight of iodine is not considered. Hence double bond equivalents can be considered as a numerical index for the total amount of unsaturated fatty acids in given oil. Five different biodiesels were prepared and their properties were measured. The double bond equivalent of each biodiesel was derived from the composition of unsaturated fatty acid methyl esters. A statistical analysis was done to relate the double bond equivalent with heating value and cetane number. From the investigation it is concluded that the heating value and cetane number decrease with increase in double bond equivalent. From the analysis, it was found that a reduction of 22.19 units (kJ/kg) in heating value can be expected for every one unit increase in double bond equivalent. Similarly it was observed that one unit increase in double bond equivalent will result in a decrease of 0.195 units in cetane number.